2022
DOI: 10.1631/jzus.b2200154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on the pregnancy outcomes of women undergoing assisted reproductive techniques (ARTs): a systematic review and meta-analysis

Abstract: The global outbreak of the coronavirus disease 2019 (COVID-19) led to the suspension of most treatments with assisted reproductive technique (ART). However, with the recent successful control of the pandemic in China, there is an urgent public need to resume full reproductive care. To determine whether the COVID-19 pandemic had any adverse effects on female fertility and the pregnancy outcomes of women undergoing ART, a systematic review and meta-analysis was conducted using the electronic Chinese and English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In comparing the pregnancy outcomes of women who underwent ART before and after the COVID-19 pandemic had begun, a systematic review and meta-analysis of papers published in Chinese and English found no significant difference in the rates of clinical pregnancy and miscarriage. The review did not assess other ART outcomes such as oocyte yield, embryo quantity, or embryo quality [14]. Like the present study, the study of Hossein Rashidi et al [15] was performed in the Iranian population, but individuals with COVID-19 were excluded from the study, and individuals without symptoms were not tested for COVID-19 infection.…”
Section: Discussionmentioning
confidence: 97%
“…In comparing the pregnancy outcomes of women who underwent ART before and after the COVID-19 pandemic had begun, a systematic review and meta-analysis of papers published in Chinese and English found no significant difference in the rates of clinical pregnancy and miscarriage. The review did not assess other ART outcomes such as oocyte yield, embryo quantity, or embryo quality [14]. Like the present study, the study of Hossein Rashidi et al [15] was performed in the Iranian population, but individuals with COVID-19 were excluded from the study, and individuals without symptoms were not tested for COVID-19 infection.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is consistent with the findings of the Rashidi nancy rate. 21,22 It is encouraging that in 2020, 85.9% of IV pregnancies were singleton, 12.9% were twins, and 1.2% were triplets. Unfortunately, currently there is no national registry of ART births in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…A third article evaluates ART cycle results before and after the COVID pandemic by analyzing seven previous studies of 33,883 ART cycles [ 65 ]. The findings of this review describe that no statistical differences were found before and after the COVID-19 pandemic for all of the studied outcomes (both clinical and laboratory).…”
Section: Discussionmentioning
confidence: 99%